A new incremental calculated approach to predict maximum contact stress of compressed packer in large deformation. (March 2022) - Fan, Peng; Kuang, Yuchun; Yang, Bo
Compressed packer rubber is large deformation material, which endures biaxial contact friction between oil-pipe and casing-pipe in sitting and sealing process. Large-deformation theory analysis of rubber brings huge difficulties to solve, this is due to the material, geometry and contact non-linearity should be considered. In this article, the deformation of compressed packer rubber tube (CPRT) is divided into free deformation, unidirectional and bidirectional constrained deformations. Based on the theory of thick-wall-cylinder and the linear constitutive of rubber material segment, the CPRT mathematical model in different deformation processes is established and the influences of axial load, axial height of CPRT and contact friction coefficient of casing inner wall etc are considered. Based on incremental calculated approach, the mathematical model is solved. By comparing the results of the theoretical model with the results of finite element method and experimental results, it is found that the theoretical maximum contact stress is more conservative than the FEM and experimental solutions, so the sealing reliability of packer effectively predicted under the premise of allowable contact stress and the theoretical results can provide a lower limit reference value for the contact stress of the packer in the actual seal process. Meanwhile, the deviation of contact stress in FEM and theoretical value at z150 height of CPRT is among 1.13%∼4.90%, which can predict the contact stress in the compressed area near the stress concentration upper end-face of CPRT under the low friction factor, the results provide a reference for the compressed packer design.